2009
DOI: 10.1177/1077801208327483
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prevention of Violence Against Women

Abstract: Practitioners in domestic violence and sexual assault programs have been encouraged by the National Center for Injury Prevention and Control to enhance their activities in violence prevention; however, many practitioners have not been trained in prevention concepts and strategies. Therefore, a needs assessment was undertaken with practitioners in the Domestic Violence Prevention Enhancement and Leadership Through Alliances and the Rape Prevention and Education programs to determine training needs. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…On the one hand, since the majority of factors associated with IPV belong to the social sphere, it is difficult to determine the health sector role and what lies beyond its responsibilities [57]. On the other hand, both public health and primary health care focus on prevention and promotion [58]. In recent decades, primary health care in Spain-and elsewhere-has become less prevention-oriented and more medicalised.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, since the majority of factors associated with IPV belong to the social sphere, it is difficult to determine the health sector role and what lies beyond its responsibilities [57]. On the other hand, both public health and primary health care focus on prevention and promotion [58]. In recent decades, primary health care in Spain-and elsewhere-has become less prevention-oriented and more medicalised.…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential for severe sequelae, including injury, death, and mental health problems, (Campbell, 2002; Ackard, Eisenberg, and Neumark-Sztainer, 2007; Johnson, Yanda, andde Vise, 2010; Wiklund, Malmgren-Olsson, Bengs, and Ohman, 2010), and an emerging focus on primary prevention, the issue of dating violence has moved to the forefront of public health injury control efforts. Over the past decade and through initiation of the CDC DELTA initiative (Domestic Violence Prevention Enhancement and Leadership Through Alliances; Martin, Coyne-Beasley, Hoehn, et al 2009; CDC, 2012), there has been a surge of interest in the development of primary prevention strategies to curb it.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment tool fills an important gap in the existing literature and is the first tool that includes specific competencies needed for sexual assault prevention in both military and civilian settings. A previous need assessment has found that practitioners working in the fields of sexual assault and domestic violence focused most of their efforts on response (e.g., counseling) rather than primary prevention and that they did not have adequate training in primary prevention despite being their interest (Martin et al, 2009). Although there are training programs for general prevention practitioners [PREVENT (Preventing Violence Through Education, Networking, and Technical Assistance) Program] (Runyan et al, 2005) and sexual assault prevention practitioners like those offered by the CDC (VetoViolence) to fill the learning gaps, there are no self-assessment tools for teams of sexual assault prevention practitioners to first identify gaps in knowledge and task assignments.…”
Section: Discussionmentioning
confidence: 99%